Social Media Engagement Effect on Brand Extension and Loyalty: Luxury and Non-Luxury Brands - Rahmadina, Dinda; Rifelly Dewi Astuti (Faculty of Economics and Business Udayana University, 2026)
This study examines the influence of Consumer Engagement (CE) on social media on Brand Extension (BExt) success and Brand Loyalty, comparing luxury and non-luxury brands in Indonesia. Addressing limited comparative evidence across these segments, a quantitative design was employed using survey data from 442 active social media users, including non-luxury brand consumers (n=215) and luxury brand consumers (n=227). Structural Equation Modeling (SEM) with SmartPLS assessed the effects of cognitive, affective, and activation dimensions of CE on attitudes toward brand extensions, extended brand loyalty, and parent brand loyalty. Results reveal significant segment differences: cognitive engagement drives extension attitudes for non-luxury brands, whereas affective engagement is more influential for luxury brands. Activation positively affects extension attitudes in both segments. Attitudes toward brand extensions significantly predict extended and parent brand loyalty. Multi-Group Analysis confirms contextual differences, offering theoretical contributions and practical implications for segment-specific social media strategies in competitive digital markets